'I was kind of teaching myself': teachers' conversations about social justice and teaching for change. Issue 2 (15th March 2017) - Burke, Anne; Collier, Diane R.
Abstract : This article shares teachers' conversations within teacher inquiry groups and considers how this reflective approach has potential for transforming teachers' practices. Conversations took place at the early stages of a longer teacher inquiry project and centred on the critical interrogation of social justice-oriented children's literature. These conversations served as a forum to help teacher professional learning communities and to reconcile understandings about social justice, action and agency within larger political and cultural forums of teaching. The teacher inquiry sessions shared in this paper explore teachers' beginning struggles with conceptualizations of social justice, and the teacher's role in imparting values to students. Teacher participants imparted their experience and practice as they negotiated their own understanding and implementation of social justice education in their schools. The teacher inquiry groups provided a needed supportive space where classroom teachers' struggles were shared alongside their beliefs and pedagogical approaches so that a social justice agenda could be achieved.